To rewrite the quadratic function \( f(x) = x^2 - 6x + 2 \) in vertex form, we will complete the square.
-
Start with the equation: \[ f(x) = x^2 - 6x + 2 \]
-
Group the \( x \) terms: \[ f(x) = (x^2 - 6x) + 2 \]
-
Complete the square:
- Take the coefficient of \( x \) (which is -6), divide it by 2 to get -3, and then square it to get 9.
- We will add and subtract 9 inside the parentheses: \[ f(x) = (x^2 - 6x + 9 - 9) + 2 \]
-
Rewrite the equation: \[ f(x) = ((x - 3)^2 - 9) + 2 \]
-
Combine the constants: \[ f(x) = (x - 3)^2 - 9 + 2 \] \[ f(x) = (x - 3)^2 - 7 \]
Now we have rewritten the function in vertex form. The final result is: \[ f(x) = (x - 3)^2 - 7 \]
Thus, the correct option is: \[ \text{f(x) = (x − 3)² − 7} \]